Assessing the Application of the Theory of Planned Behaviour to Water Usage During and Following a Water Crisis - Herr, Donna (Department of Psychology, 2024)
The global frequency and severity of water scarcity events are increasing, making it necessary to reduce human demand for available water supplies. This mixed-methods research used the Theory of Planned Behaviour (TPB) to investigate determinants of water usage during and after a water crisis. 89 participants were surveyed in Cape Town, South Africa, during the 2018 water crisis, followed by 56 repeated participants 25 months later. The study found that perceived behavioural control was the only significant determinant of actual water usage. A validation sample of 156 participants was also collected at the second time point, and the potential impact of the Coronavirus Disease 2019 (COVID-19) pandemic on the follow-up study was addressed. A TPB questionnaire was created, assessed for reliability and validity, and piloted before use before the first wave of study among a sample of the target population (N = 28). Structural Equation Modelling was used to test the predictive value of the TPB at both time points, and a comparison of the models was reported. This research adds to the existing literature on the TPB by addressing two suggested limitations of past research: (1) a lack of consideration of confounding research contexts and (2) issues of construct validity in current TPB research methods